Arial movement - Yeadon, M. R. (Biomechanics in sport, 2000)
Most sports movements contain an aerial phase during which the body loses contact with the ground or apparatus. While the path of the mass centre during flight is determined by its location and velocity at takeoff, the amount and type of rotation of the body is largely under the control of the athlete. Somersault rotation is a consequence of the angular momentum generated during takeoff. Twist rotations may be initiated during takeoff or during the aerial phase by means of asymmetrical arm or hip movements. Asymmetrical arm movements may be used to stop the twist in a twisting somersault or to prevent the build-up of twist in a non-twisting somersault. The control of the twist in this way is possible using feedback via the inner ear balance mechanisms provided that the somersault rate is not too high.